DEVELOPING AUDIO-VISUAL MEDIA BY USING ANIMAKER FOR TEACHING SPEAKING TO FOURTH-GRADE STUDENTS OF SDS ISLAM ASH-SHOLIHAH MEDAN - Bukhari Zul Fadhli; Indra Hartoyo (Universitas Negeri Medan, 2023)
The researcher has found a problem that speaking skills learning is not optimal because of inappropriate media that are used in online learning. Therefore, most students do not have the ability to speak or respond to the oral question directly even, it is just a greeting. The study's methodology is grounded in R&D efforts in the field of education. In their model, Gall et al. (2003) The study's findings utilized to build or design new items in certain methods. Then they were rigorously field-tested, assessed, and refined until they met the required requirements of efficacy, quality, or a comparable level. The way to make AVM suitable for this, is by the process of collecting data to gain student needs. By the process of collecting data in terms of studentsâ€™ necessities, lacks, and wants, the researcher knows how to build a material as a content of this AVM. The way how Animaker develop the AVM is Animaker have an advantage to support AVM become interesting and suitable. By the diversity of template, background, transition, and character, Animaker has succeed to support and develop AVM to interpret what the studentsâ€™ need. In fact, this AVM gained score 89% which indicated â€œexcellentâ€Keywords: Speaking, Audio-Visual Media, Animaker